KESAHIHAN MATAN HADIS MENURUT M. SYUHUDI ISMAIL - Idris Siregar (UIN Sumatera Utara Medan, 2020)
The Hadith occupies the second position after the Koran in Islamic law. Because, one function of the hadith of the Koran is as Bayan or the explanatory of the Koran. Knowledge of prudence and a isnaad is indispensable in the research of hadith, because if the Isnaad Sahih Hadith can not be sure the eyes are also valid, or if the Sahih Hadith can not be ensured the its isnaad is also Sahih. o get a true understanding of hadith, the scholars have done business in researching the A Isnaad and the hadith. The scholars have struggled to devote all its ability to analyze and standardize in researching the validity of a hadith. In this case, Indonesia has one of the leading scholars namely M. Syuhudi Ismail, he gave the standardization of the validity of the hadith in the Mahakaryanya: The validity method of hadith and critical study review with the historical science approach. Understand the hadith by seeing the status of the Sanad, see the There are and the content of the hadith is the offer Syuhudi in researching the Hadith.